A Feasibility Study on the Establishment of Flower Express at Dangwa Flower Market #1318 Stall G, Sampaloc, Manila (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The Flower Express is a product and service business located at Dangwa Flower Market #1318 Stall G Barangay 456 Dos Castillas Street Sampaloc, Manila. It’s a rental stall in Dangwa Flower Market. The Flower Express sells a wholesale and retail fresh cut flowers coming from different country like Thailand, Netherlands, Ecuador, etc. The Flower Express also arrange flowers from different kinds of occasion like birthday, wedding, anniversary and graduation days especially every peak seasons like Valentine’s Day, All Saints Day, Holy Week, Mother’s Day and a month of December. The study adopted a descriptive and quantitative type of research. Detailed research instruments were developed and pretested before they were administered. The number of samples was 100 which stand as a variance for the general population; this variance was definitely obtainable and applicable for a statistical testing. The target places were schools, supermarkets and churches along Sampaloc, Manila. The main instrument of the study was survey questionnaires were designed and administered. Other method that was used is the personal or Face to Face interview, which the response rate was usually high as the respondent typically found it difficult to refuse an interviewer face to face.The survey results affirm the four aspects of the Plan, the marketing viability which concluded the place of the business is accessible for the target market and making it a strategic place for business. The technical viability which all government ordinances can be easily obtained, the management viability the human resource capital are available in the area. And lastly, the financial viability in the financial simulation shows the liquidity of the quick return of investment. The flower industry is booming in the country, for Filipinos never forget special occasion such as loved ones’ birthdays, anniversary and a lot more. Our culture teaches us the value of respecting elders by giving something whichever possible, it gives us the feeling of joy and care for one another. Thus, it strengthen the lies between families. The Flower Express shop intends in a most appropriate occasion. Floristry, nowadays, is one of the higher industries in many developing and underdeveloped industries. Flower shop’s now is easily located in supermarkets, flower markets, garden supply and online shops.
Keywords: flower, flower markets, aspects of the plan